Synthesis and Antimicrobial Activity of Some Novel Chalcones - Rajendra Prasad, Y.; Laxmana Rao, A.; Murali, K.; Ravi Kumar, P. (Asian Journal of Chemistry, 2010)
Five novel chalcones have been prepared by condensation of 2-hydroxy-1-acetonaphthone with different aromatic aldehydes in 30% alkali. The compounds obtained were identified by spectral data and screened for antimicrobial activity.